'It Opened My Eyes'—examining the impact of a multifaceted chlamydia testing intervention on general practitioners using Normalization Process Theory. (28th March 2018) - Yeung, Anna; Hocking, Jane; Guy, Rebecca; Fairley, Christopher K; Smith, Kirsty; Vaisey, Alaina; Donovan, Basil; Imrie, John; Gunn, Jane; Temple-Smith, Meredith; ,
Abstract: Background: Chlamydia is the most common notifiable sexually transmissible infection in Australia. Left untreated, it can develop into pelvic inflammatory disease and infertility. The majority of notifications come from general practice and it is ideally situated to test young Australians. Objectives: The Australian Chlamydia Control Effectiveness Pilot (ACCEPt) was a multifaceted intervention that aimed to reduce chlamydia prevalence by increasing testing in 16- to 29-year-olds attending general practice. GPs were interviewed to describe the effectiveness of the ACCEPt intervention in integrating chlamydia testing into routine practice using Normalization Process Theory (NPT). Methods: GPs were purposively selected based on age, gender, geographic location and size of practice at baseline and midpoint. Interview data were analysed regarding the intervention components and results were interpreted using NPT. Results: A total of 44 GPs at baseline and 24 at midpoint were interviewed. Most GPs reported offering a test based on age at midpoint versus offering a test based on symptoms or patient request at baseline. Quarterly feedback was the most significant ACCEPt component for facilitating a chlamydia test. Conclusions: The ACCEPt intervention has been able to moderately normalize chlamydia testing among GPs, although the components had varying levels of effectiveness. NPT can demonstrate the effective implementation of an intervention in general practice and has been valuable in understanding which components are essential and which components can be improved upon.